Unearthing Ourselves Upon Prison Release: Corporal Practices and the Pursuit of Health - Chesnay, Catherine (Revue générale de droit, 2017)
Recent feminist scholarship on prison release has demonstrated that, upon incarcerated women’s release from prison, they are not quite free from the criminal-justice system, as they carry with them the imprint of their time spent in prison. Using data from interviews and a focus group from a study informed by participatory action research, this article explores how participants attempted to “undo” the imprint of penal governance on their bodies and health. Through the exploration of corporal practices, such as taking care of their appearance, using psychoactive medications, and defecating, this article shows how women attempt to “undo” prison in order to pursue health. It concludes that corporal practices may help them to partially unearth themselves from prison.